Quantitative Evaluation of Oxidation Time, Dilute Acid Concentration and Acid Type on Indigo Yield from Indigofera Leaves: An Ethnochemical Approach to Sustainable Batik Dyeing - Amar Mualimin; Khoeurn Kimleang; Hyung Jun Jo (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: This study aims to analyze the effect of oxidation time, dilute acid concentration, and type of acid on the indigo content produced, as well as to determine the effect of the color-covering agent (mordant) on the color quality of batik cloth using natural dyes from the indigo plant (Indigofera). Methodology: Analytical balance (Ohaus Pioneer), Pyrex beaker glass and volumetric flask, aeration system with Resun LP-40 air pump, pH indicator strips (Merck), and UV-Vis spectrophotometer (Shimadzu UV-1800) were used. Experimental laboratory method with oxidation-time and acid-variation design was applied. Data were processed using Microsoft Excel 2019 and SPSS 25. Literature review and observational approach supported analysis. Main Findings: Indigo content increased with longer oxidation time, reaching 23.78 ppm at 12 hours. The optimal acid concentration was 0.01 M HCl (26.88 ppm), while 0.1 M significantly reduced yield (15.77 ppm). Sulfuric acid 0.01 M produced the highest indigo level (29.20 ppm). Mordant variation affected color quality: tunjung produced darker bluish-green tones, lime produced lighter blue, and alum maintained the original blue shade. Novelty/Originality of this study: This study integrates ethnochemical perspectives with quantitative chemical analysis by systematically examining oxidation time, dilute acid concentration, acid type, and mordant effects within a traditional Indigofera-based batik framework. It advances knowledge by scientifically validating indigenous dyeing practices while providing measurable parameters to optimize natural indigo production and improve sustainable textile applications.